Women Empowerment through Micro, Small and Medium Enterprises Rubik Ganepo in 50 Kota Regency - Rizky, Maulidia; Bakhtiar, Yusnanik; Fatmariza, Fatmariza; S, Nurman (Borneo Novelty Publishing, 2024)
This study aims to describe women's empowerment through Rubik Ganepo UMKM in Jorong Padang Kandi and explain the supporting and inhibiting factors of women's empowerment and the impact of women's empowerment through Rubik Ganepo UMKM in Jorong Padang Kandi. This study uses a qualitative type. We collected data for this study through observation, interviews, and documentation studies. The purposive sampling method and source triangulation techniques determined the informants in this study and tested data validity. The study employed qualitative data analysis techniques throughout the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that women's empowerment through the Rubik Ganepo UMKM group utilizes local resources, namely cassava, which is processed into Rubik Ganepo. Supporting factors are natural resources, family support, high solidarity, facilities, and infrastructure. The obstacles are technology, quality of human resources, women's position, and capital. Implementation through the Rubik Ganepo UMKM group is able to increase independence, knowledge, and social life with the community. In Jorong Padang Kandi, women who were previously housewives now play a more significant role as breadwinners, enhancing their dignity and status and empowering them at all levels of society.